Pengaruh Citra Merek, Kualitas Produk, dan Product Knowledge terhadap Repurchase Intention pada Gongso Kopi - Ilham Hadzafi, Aldo; Arifin, Samsul (Universitas Nahdlatul Ulama Surabaya, 2024)
This study was used to explore the influence of brand image, product quality, and product knowledge on repurchase intentions at Gongso Kopi. This research uses quantitative data in the form of numbers (numerics). This data was obtained from primary and secondary sources. Consumers who buy drinks and food at Gongso Kopi Jepara are the population in this research. Sample determination was carried out using the Purposive Sampling technique (samples were selected based on certain criteria). Data collection in this study was carried out by distributing questionnaires which were equipped with a Likert scale as a measuring tool. The data analysis technique uses a multiple regression analysis approach. Through the process of analyzing data, researchers found that the brand image variable had a positive and significant influence on repurchase intentions at Gongso Kopi. The product quality variable also has a positive and significant influence on repurchase intentions at Gongso Kopi. Apart from that, the product knowledge variable also has a positive and significant effect on repurchase intentions at Gongso Kopi.